Sequências didáticas produzidas por professores alfabetizadores: (re)significação do processo de formação docente - Aguiar Júnior, Dejair Batista de (2019)
This work aimed to investigate the nature of the teaching work, in relation to the underlying language conception in the planning of Didactic Sequences (hereinafter SD) produced and applied by teachers in classes of the initial years of Elementary Education, that is, as the language abilities were contemplated and performed in the classroom through the sequences, in order to analyze how the teacher's practice is configured. In the teaching-learning context, working with language presupposes a theoretical-practical alignment based on a diagnosis of reality, due to the need for coherent and meaningful teacher interventions to the actual student demands. The didactic sequences analyzed were elaborated by 12 teachers from a public elementary school in a city in the south of Minas Gerais in the meetings of the National Pact for Literacy in the Right Age (PNAIC) program in 2013, 2014 and 2015. For the analysis of language abilities, the criteria and categories of classification proposed by the linguists of the current sociodiscursive interactionist (ISD) were adopted as indicators. The research, therefore, was anchored in the qualitative paradigm and, in addition, it was based on the theoreticalmethodological principles of ISD. uch a methodological approach presupposes the relevance of the reflexive teacher training process, whose performance is essential in the process of developing CL necessary for reading and producing text. For the analysis of the data an interpretative approach was adopted, based on the methodological path proposed by the Grounded Theory.